Wind of change? Cultural determinants of maternal labor supply - Boelmann, Barbara,Raute, Anna,Schönberg, Uta (School of Economics and Finance, Queen Mary University of London, 2020)
Does the culture in which a woman grows up influence her labor market decisions once she has had a child? To what extent might the culture of her present social environment shape maternal labor supply? To address these questions, we exploit the setting of German reunification. A state socialist country, East Germany strongly encouraged mothers to participate in the labor market full-time, whereas West Germany propagated a more traditional male breadwinner-model. After reunification, these two cultures were suddenly thrown together, with consequent increased social interactions between East and West Germans through migration and commuting. A comparison of East and West German mothers on both sides of the former Inner German border within the same commuting zone shows that culture matters. Indeed, East German mothers return to work more quickly and for longer hours than West German mothers even two decades after reunification. Second, in exploiting migration across this old border, we document a strong asymmetry in the persistence of the culture in which women were raised. Whereas East German female migrants return to work earlier and work longer hours than their West German colleagues even after long exposure to the more traditional West German culture, West German migrants adjust their post-birth labor supply behavior nearly entirely to that of their East German colleagues. Finally, taking advantage of differential inflows of East German migrants across West German firms in the aftermath of reunification, we show that even a partial exposure to East German colleagues induces
10419/247183
Keywords: Graue Literatur; cultural transmission; social norms; maternal labor force participation; German reunification